Seminar Smart Parenting di Era Digital - Aufia Aisa; Rina Dian Rahmawati; Amrini Shofiyani; Muhammad Subhan; Evi Endha Lestari; Fahmi Najah Umami; Ummi Nur Jannah (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2024)
The lack of understanding of the Gambiran Village community regarding smart parenting in forming children's character in the digital era is the basis for holding a "Smart Parenting Seminar in the Digital Era". The targets of this activity are posyandu members and PKK cadres in Gambiran Village. There were 10 participants in this seminar which was held at the Gambiran Village Hall, as well as Mrs. Aufia Aisa M.Pd.I as the resource person in this seminar. It is hoped that this education will have a positive influence, can motivate parents, posyandu members and PKK cadres in Gambiran Village to continue learning and be able to overcome the problems faced regarding parenting in the digital era. The method for implementing community service activities includes the lecture method, namely seminars, using the CBR (Community Based Research) approach. The results provided from this workshop activity are in the form of a pocket book about understanding smart parenting in the digital era which includes the introduction of technology, restrictions and supervision for children that is easy to understand and learn at any time.